Studi Pemikiran Prof. Dr. Muhammad Sayyid Thanthawi Interpretasi Atas Pemberlakuan Suku Bunga Bank - Dwi Umardani (ITB AAS INDONESIA Surakarta, 2021)
Abstract This study aims to find out any further opinion of a contemporary muslim figure named Muhammad Sayyid Thantawi regarding the law of bank interest rate. The method used is qualitative method with primary and secondary data collected through literature review then analyzed in depth to get clear-cut the thing being studied. According to him, since the determination of profit in advance in the form of profit-sharing ratio is not based on the argument of Al-Qur'an or Al-Hadith, there is no argument in either Al-Qur'an or Al-Hadith that prohibits the determination of profit in advance in the form of a certain percentage level of capital, the determination of profit in advance at a certain percentage level of capital can prevent the capital owner from fraud, there is no element of exploitation in the practice of bank interest rate, and the considerations of maslahah value, the practice of bank interest rate does not include riba and is lawful. Keywords: Bank interest rate, no element of exploitation, lawful.